2018
DOI: 10.1007/s13197-018-3325-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection of non-Saccharomyces yeasts for orange wine fermentation based on their enological traits and volatile compounds formation

Abstract: In order to select the non- yeasts for orange wine fermentation, the enological traits and volatile compounds formation of ten non- yeast strains were evaluated through physicochemical methods and solid-phase microextraction coupled to GC-MS, respectively. The results indicated that non- yeast fermentation had lower maximum populations (7.8-8.0 Log cfu/mL), longer fermentation period (7-10 days), lower ethanol (4.13-7.79%), lower total acids (7.48-8.51 g/L) and higher volatile acids concentrations (0.08-0.23 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…It plays an important role in diversity of tastes and flavors with established qualities (Abe et al, 2019). Pichia was considered as non-alcoholic yeast during the liquor making process, mainly used to produce volatile compounds in liquor (Mónaco et al, 2016;Hu et al, 2018). The previous research found that Pichia could degrade lactic acid and upregulate the microbial metabolic activity of ethanol in S. cerevisiae under lactic acid stress (Mónaco et al, 2014;Yamamoto et al, 2019;Deng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in diversity of tastes and flavors with established qualities (Abe et al, 2019). Pichia was considered as non-alcoholic yeast during the liquor making process, mainly used to produce volatile compounds in liquor (Mónaco et al, 2016;Hu et al, 2018). The previous research found that Pichia could degrade lactic acid and upregulate the microbial metabolic activity of ethanol in S. cerevisiae under lactic acid stress (Mónaco et al, 2014;Yamamoto et al, 2019;Deng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Agilent 6890N gas chromatography (Agilent 6890N, Agilent Technologies Inc., Shanghai, China) on an HP-5 capillary column (30 m × 0.32 mm × 0.25 µm) coupled to an Agilent 5975B mass spectrometer was used to analyze the extracted volatile aroma compounds. The extraction, analysis, and identification of volatile aroma compounds were conducted as described by Hu et al [24]. The odor active value (OAV), calculated as the ratio between the concentration of flavor compound to its odor threshold (OT), was used to obtain odor patterns.…”
Section: Hs-spme/gc-ms Analysis Of Volatile Aroma Compoundsmentioning
confidence: 99%
“…The sensory evaluation of citrus wine was conducted by a trained panel consisting of nine panelists (five females and four males) from Huazhong Agricultural University. The sensory evaluation of citrus wine was performed as described by [24].…”
Section: Sensory Evaluation Of Citrus Winementioning
confidence: 99%
“…The most characteristic compounds produced by Hanseniaspora spp. that confer positive aroma to wines are acetate esters (isoamyl acetate, ethyl hexanoate, ethyl caprylate, phenylethyl propionate, ethyl caprate, ethyl 9-decenoeate, ethyl acetate, phenethyl acetate, beta-phenylethyl acetate, benzyl acetate and 2PA) [ 50 , 52 , 53 , 54 ] and aldehydes, such as acetaldehyde, benzaldehyde, 4-ethylbenzaldehyde and benzene acetaldehyde [ 50 ]. In addition, some alcohols (glycerol, 1-pentanol, phenethyl alcohol, benzyl alcohol), carboxylic acids (hexanoic acid, octanoic acid) and terpenes (limonene) are implicated in the wine flavors [ 50 , 52 ].…”
Section: Non-saccharomyces Speciesmentioning
confidence: 99%